(untitled) (Journal of Legal Studies, 2015)
At the conclusion of the transport contract for goods or people, the carrier shall make available to the consignor or the passenger his exclusive and special service to travel in space with a suitable means of transport, different from other previous or subsequent transport services. Thus, the transport activity is entirely distinct and independent from the civil or economic transactions concerning the goods transported, which run between the consignor and the recipient, or, taking another example, from the insurance agreement during the transport of goods or persons, imposed by law. At the same time, transport is a service of public interest, which obliges the transport operator to publish permanently his transport offer with all the information needed to access it. This is the source of the organized and uniform periodicity of the carrying trade, performed as a constant preoccupation in order to obtain profit. But, because of the multitude and diversity of displacement interests of the transport beneficiaries, sometimes the transport operator is forced to arrange that the transport of goods or people contracting should be carried out through another carrier. Therefore, whenever the transporter is substituted by another transport operator for total or partial execution of its duty, the latter will be considered part of the transport contract, taking over all obligations of the contracting operator directly with the beneficiary of his service.